RESEARCHES OF MODERN APPROACHES OF PROVIDING CONSTRUCTION BY WORKERS - Radkevich, A. V.; Novokhatʹko, E. Yu. (Science and Transport Progress, 2010)
The influence of resource provision on determination of the production capacity of construction organization is studied.